Philosophy and Digital Humanities in Slovakia - Problem of Digital Textual Resources - Andrej Gogora (Communications - Scientific letters of the University of Zilina, 2018)
The main aim of the article is to bring together free available digital textual resources of Slovak philosophy into the comprehensive list that will serve as a basis for a more systematic building of databases of resources in the future. Firstly, it consists of mapping and describing of accessible Slovak philosophical digital resources. Secondly, it illustrates methodological benefits of digital resources in digital scholarship in philosophy. The purpose of contribution is to draw attention to systematic building-up of digital textual resources in Slovak philosophy and to demonstrate the importance of the application of advanced computational processes to digital textual resources in Slovak philosophy for the purpose of digital as well as traditional armchair philosophical research.